The secondary metabolites produced by Lactobacillus plantarum downregulate BCL-2 and BUFFY genes on breast cancer cell line and model organism Drosophila melanogaster: molecular docking approach. - Sentürk, M.; Ercan, F.; Yalcin, S. (Cancer Chemotherapy and Pharmacology, 2020)
The current study was designed to evaluate the toxicity of the secondary metabolites of Lactobacillus plantarum against the human breast cancer cell line (MCF-7) and the Drosophila melanogaster. In this study, toxicity analyses of secondary metabolites of Lactobacillus plantarum were analyzed on breast cancer cells, and the Drosophila melanogaster. After application, in the MCF-7 cell line, expression levels of RRAS-2, TP53, BCL-2, APAF-1, CASP-3, FADD, CASP-7, BOK genes; in D. melanogaster; expression levels of RAS64B P53, BUFFY, DARK, DECAY, FADD, DRICE, and DEBCL genes were determined by RT-PCR. In addition, analysis of L. plantarum secondary metabolite was performed by GC-MS method and molecular binding poses of secondary metabolites and human enzymes were investigated in silico. Drosophila melanogaster being used as a model organism where some of the human genes were preserved. The IC50 value of the secondary metabolite in the MCF-7 cell line was determined to be 0.0011 mg/ml. Lethal concentration 50 (LC50) and 99 (LC99) values of secondary metabolites against fruit fly adults were 0.24 mg/ml and 0.54 mg/ml, respectively. The expression levels of BCL-2 and BUFFY genes which are anti-apoptotic in human and fruit flies have been reduced, and at the same time, increased expression of DECAY, FADD, RAS64B apoptotic genes in D. melanogaster. The substance detected in the secondary metabolite content and encoded as L13 (3-phenyl-1, 2, 4-benzotriazine) has been observed to have high binding affinity in the studied genes.